The synergistic effect of thiourea and surfactants on corrosion inhibition of stainless steel-316 in hydrochloric acid - Ullah, S. (Trans Tech Publications Ltd, 2014)
Corrosion and scaling are the common problems to all the industries. A remedy of these problems was sought out through chemical treatment: indigenously available raw materials including thiourea, surfactants (cationic, anionic and nonionic containing pre, critical and post micellar concentration). Evaluation of corrosion inhibition properties stainless steel 316 by thiourea based inhibitor and its synergistic effect with cationic cetyl tri-methyl ammonium bromide (CTAB), anionic sodium dodecyl sulphate (SDS) and nonionic triton X-100 have been carried out by weight loss method as a function of concentration of thiourea and surfactants. These materials were applied to the coupons of stainless steel 316 in different acidic concentration. Corrosion rates were calculated using weight loss method. Excellent results were achieved regarding corrosion inhibition in the presence of thiourea and surfactants assuring the better performance of these chemicals. The results showed that corrosion rate was decreased from 90 mpy to 12.1 mpy after 720 hours by the addition of 200ppm thiourea in critical micellar concentration of SDS in 3M HCl acid solution. Â© (2014) Trans Tech Publications, Switzerland.